REQUIREMENTS FOR GRADUATES OF COMPANIES - LUKACOVA, Danka (Trends in education, 2014)
The Department of Technology and Information Technology PF University in Nitra, in cooperation with UCM in Trnava project designed 021UKF-4/2014 Remote real experiments in school practice. One of the objectives of the project, a survey of companies requirements for knowledge and skills graduates. In this paper the author presents the results of a questionnaire survey in companies.
Keywords: companie; graduate; requirements.